Ancient synagogues-archaeology and art : new discoveries and current research - Hachlili, Rachel. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2013)
Ancient Synagogues - Archaeology and Art. New Discoveries and Current Research presents archaeological evidence - the architecture, art, Jewish symbols, zodiac, biblical tales, inscriptions, and coins - which attest to the importance of the synagogue. When considered as a whole, all these pieces of evidence confirm the centrality of the synagogue institution in the life of the Jewish communities all through Israel and in the Diaspora. Most importantly, the synagogue and its art and architecture played a powerful role in the preservation of the fundamental beliefs, customs, and traditions of the Jewish people following the destruction of the Second Temple and the loss of Jewish sovereignty in the Land of Israel. The book also includes a supplement of the report on the Qazion excavation.